2017
DOI: 10.2147/jep.s126146
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and gastric emptying inhibitory effect of herbal <em>Melia azedarach</em> leaf extract in rodent models of diabetes type 2 mellitus

Abstract: Diabetes type 2 is associated with impaired insulin production and increased insulin resistance. Treatment with antidiabetic drugs and insulin strives for normalizing glucose homeostasis. In Ethiopian traditional medicine, plant extracts of Melia azedarach are used to control diabetes mellitus and various gastrointestinal disorders. The objective of this study was to clarify the antidiabetic effects of M. azedarach leaf extracts in diabetic type 2 experimental animals. In this study, mice were injected with Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Since 1943, it was found to have toxicological effects on pancreatic b-cells leading to diabetogenic action, therefore (Jacobs, 1937;Pincus, 2013) is commonly employee for the development of Type-I Diabetes Mellitus in animal models. (Carvalho et al, 2003;Dunn et al, 1943;Goldner and Gomori, 1943;Lenzen and Panten, 1988;Saadia et al, 2005;Saleem Mir et al, 2013;Seifu et al, 2017;Shaw Dunn and Mcletchie, 1943;Szkudelski, 2001;Webb, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1943, it was found to have toxicological effects on pancreatic b-cells leading to diabetogenic action, therefore (Jacobs, 1937;Pincus, 2013) is commonly employee for the development of Type-I Diabetes Mellitus in animal models. (Carvalho et al, 2003;Dunn et al, 1943;Goldner and Gomori, 1943;Lenzen and Panten, 1988;Saadia et al, 2005;Saleem Mir et al, 2013;Seifu et al, 2017;Shaw Dunn and Mcletchie, 1943;Szkudelski, 2001;Webb, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…It increased glucose-6-phosphate dehydrogenase activity and hepatic, skeletal muscle glycogen content, after 21 days of treatment. The study revealed the regeneration of insulin-producing cells and a corresponding increase in the plasma insulin and c-peptide levels with the treatment [ 60 ] Melia azedarach L. Mahaneem (S), Bakain (H), Persian lilac (E) Tree (W/C)/all parts Azedarachic acid ( 15 ), nicotinic acid, gallic acid, para-coumaric acid, vanillic acid, chlorogenic acid, syringic acid, caffeic acid, ferulic acid, fatty acids (caproic, palmitic, stearic, oleic, linoleic, and linolenic acid) [ 61 ] The decoction of aerial parts is taken in the morning (1) Bioassay-guided fractions and isolates of fruits and leaves showed inhibitory effects on protein tyrosine phosphatase-1B enzyme as well as glucose uptake stimulation on C 2 Cl 2 myoblasts cells in vitro [ 62 ] (2) Aqueous leaf extracts (300, and 400 mg/kg, intraperitoneal) displayed anti-diabetic on type 2 mice [ 63 ] Menispermaceae Cissampelos pareira L. Patha (S), midwife’s herb (E), Padi/Parh (L) Climber (W/C)/whole plant Pelosine, l -curine, hayatinine, hayatidine, cissampareine, cissamine, dicentrine, cycleanine, insularine, cycleanine, nuciferine, bulbocarpine, corytuberine, magniflorine, norimeluteine, pareitropone, berberine (8), reserpine [ 64 ] The dried root powder (half teaspoon) is taken with water once a day for 40 days The hydro-alcoholic leaves extract (200 and 400 mg/kg, p.o.) showed anti-diabetic activity by decreasing fasting blood glucose and increasing the body weight of on STZ-induced diabetic rats when compared to glibenclamide (5 mg/kg) [ 65 ] Stephania glabra (Roxb.)…”
Section: Resultsmentioning
confidence: 99%
“…(2) Aqueous leaf extracts (300, and 400 mg/kg, intraperitoneal) displayed anti-diabetic on type 2 mice [ 63 ]…”
Section: Resultsmentioning
confidence: 99%
“…These samples are analyzed with regard to glucose and insulin to generate dynamic profiles in the absence and presence of the study compound. Preclinically, the glucose protocols differ slightly from other glucose administrations (e.g., intraperitoneal), different duration of, or no, fasting prior to glucose challenge, but, most importantly, sometimes only measuring glucose …”
mentioning
confidence: 99%
“…Preclinically, the glucose protocols differ slightly from other glucose administrations (e.g., intraperitoneal), different duration of, or no, fasting prior to glucose challenge, but, most importantly, sometimes only measuring glucose. [6][7][8] Pharmacometric analysis based on time-course data is increasingly used in drug development, due to its integrative nature and the ease with which it can handle dynamic relationships. [9][10][11] There are several examples in which pharmacometric analysis has been shown to be highly powerful in phase II trials.…”
mentioning
confidence: 99%